Perancangan Aplikasi E-Commerce Spare-Part Komputer Berbasis Web Menggunakan CodeIgniter Pada Dhamar Putra Computer Kota Tangerang - Nurul Musthofa; Mochamad Adhari Adiguna (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
The use of the internet is increasingly widespread and leads to the business world starting to use the internet as a medium for selling and buying. Dhamar Putra Computer is a company engaged in the field of computer spare parts, where customers purchase products by directly coming to the Dhamar Putra Computer store. To provide a solution, e-commerce is created where customers can buy products easily without having to come to the store, and companies can more easily provide information to customers which will affect selling power. In the development of e-commerce, the author uses the waterfall method, as for the design using UML (Unified Modeling Language) which consists of use case diagrams, activity diagrams and sequence diagrams. For database design using ERD (Entity Relationship Diagram), while in making the web, the author uses the PHP programming language and framework CodeIgniter version 3 and MySQL as the database media. Keywords: E-Commerce, Waterfall, PHP, UML, CodeIgniter, MySQL